Broken intraocular lens during cataract surgery. Issue 8 (August 1992) - Kirkpatrick, J N; Cook, S D
Abstract : A case of planned routine extracapsular cataract extraction is described where surgery was complicated peroperatively by fracture of the posterior chamber lens implant. The technique of lens implantation is discussed.